2023
DOI: 10.3389/fonc.2023.1137803
|View full text |Cite
|
Sign up to set email alerts
|

Validation of clinical acceptability of deep-learning-based automated segmentation of organs-at-risk for head-and-neck radiotherapy treatment planning

Abstract: IntroductionOrgan-at-risk segmentation for head and neck cancer radiation therapy is a complex and time-consuming process (requiring up to 42 individual structure, and may delay start of treatment or even limit access to function-preserving care. Feasibility of using a deep learning (DL) based autosegmentation model to reduce contouring time without compromising contour accuracy is assessed through a blinded randomized trial of radiation oncologists (ROs) using retrospective, de-identified patient data.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…These methods promise potential time-savings for target delineation and treatment planning. 13 , 14 Automation, namely deep learning and artificial intelligence (AI) approaches, have been increasingly common in medicine over the past decade, 15 although these have focused on workflows, staffing, and funding in high-income regions.…”
Section: Introductionmentioning
confidence: 99%
“…These methods promise potential time-savings for target delineation and treatment planning. 13 , 14 Automation, namely deep learning and artificial intelligence (AI) approaches, have been increasingly common in medicine over the past decade, 15 although these have focused on workflows, staffing, and funding in high-income regions.…”
Section: Introductionmentioning
confidence: 99%
“…As deep learning-based auto-contouring methods for head-and-neck OARs have been shown to offer satisfactory geometric performance [10] , [6] , the next step is to evaluate their dose impact [11] . However, we observed that dose-based studies on auto-contours tend to use either smaller ( ) [12] , [13] , [14] , [15] , [16] , [17] , [18] or medium-sized ( ) [19] , rather than larger [20] datasets. Studies using larger datasets simply superimpose the automated contours on the clinical dose [20] which does not fully replicate the treatment planning process.…”
Section: Introductionmentioning
confidence: 82%
“…This work aimed at proposing and assessing an automated plan optimization workflow for retrospective studies that can be easily implemented by clinics due to its use of existing clinical resources. Unlike previous works [12] , [13] , [14] , [15] , [16] , [17] , [18] , we performed this at large-scale and for both photon and proton radiotherapy. To replicate our approach, a clinic can simply use the scripting interface of their treatment planning system (TPS) and convert their planning process into a step-by-step approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized and precise organ at risk (OAR) contours are essential for head and neck (HN) radiation therapy, enabling safe treatments and more consistent dose reporting ( 1 ). While manual contouring is time-consuming and prone to user variation, Deep learning (DL) autocontouring methods have demonstrated time savings ( 2 , 3 ) and reduced variation ( 4 , 5 ) compared to manual contouring methods. Autocontouring tools generally perform well, however, a variety of clinically relevant failures, ranging from minor to severe, do occur with no warning given from the model-hosting tool ( Supplementary Figure S1 ).…”
Section: Introductionmentioning
confidence: 99%